The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/slct.202203426
|View full text |Cite
|
Sign up to set email alerts
|

Effective Removal of Nitrogenous Pesticides from Water Using Functionalized Calix[4]arene‐Decorated Magnetite Nanoparticles

Abstract: An effective nano-adsorbent has been synthesized by the modification of magnetite nanoparticles with ionic-liquid modified calix[4]arene through covalent linkage. This nanocomposite was used for the removal of amino-functionalized nitrogenous pesticides, metribuzin (MET), and dicloran (DIC) from an aqueous solution through adsorption. The adsorption studies showed that the synthesized nanomaterial was effective in removing these pollutants from an aqueous solution. The maximum adsorption capacity for MET and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, [66–74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Resultsmentioning
confidence: 99%
“…Decreasing the efficiency by increasing the number of steps can be related to the saturation of adsorbent sites or damage to sites active in the adsorbent. [64,65] In previous studies, [66][67][68][69][70][71][72][73][74] the reuse of synthesized materials has been investigated and it has been shown that synthesized compounds also can be recycled.…”
Section: Adsorbents Recyclementioning
confidence: 99%